2009
DOI: 10.4204/eptcs.4.2
|View full text |Cite
|
Sign up to set email alerts
|

An Exponential Lower Bound on OBDD Refutations for Pigeonhole Formulas

Abstract: Haken proved that every resolution refutation of the pigeonhole formula has at least exponential size. Groote and Zantema proved that a particular OBDD computation of the pigeonhole formula has an exponential size. Here we show that any arbitrary OBDD refutation of the pigeonhole formula has an exponential size, too: we prove that the size of one of the intermediate OBDDs is Ω(1.025 n ).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
4
8
0
Order By: Relevance
“…Finding f (G, c) allows to determine the corresponding parameter in matrices and to prove the conjecture of Tveretina et al in [6]. In particular, our result f (n) = (1 − 1 √ 2 )n is an improvement of the previously known bound f (n) ≥ 1 2 (1 − 1 √ 2 )n from [6]. This in turn improves the lower bound on resolution for ordered binary decision diagrams.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Finding f (G, c) allows to determine the corresponding parameter in matrices and to prove the conjecture of Tveretina et al in [6]. In particular, our result f (n) = (1 − 1 √ 2 )n is an improvement of the previously known bound f (n) ≥ 1 2 (1 − 1 √ 2 )n from [6]. This in turn improves the lower bound on resolution for ordered binary decision diagrams.…”
Section: Introductionsupporting
confidence: 63%
“…
Motivated by the problem in [6], which studies the relative efficiency of propositional proof systems, 2-edge colorings of complete bipartite graphs are investigated. It is shown that if the edges of G = K n,n are colored with black and white such that the number of black edges differs from the number of white edges by at most 1, then there are at least n(1 − 1/ √ 2) vertex-disjoint forks with centers in the same partite set of G. Here, a fork is a graph formed by two adjacent edges of different colors.
…”
mentioning
confidence: 99%
“…Lemma 1 was presented for the first time in [16], but with a smaller coefficient c = 1 2 − 1 4 √ 2 ≈ 0.146. This lemma is of interest from a point of view of Ramsey Theory that typically asks questions of the form: How many elements of some structure must there be to guarantee that a particular property will hold?…”
Section: Technical Lemmasmentioning
confidence: 99%
“…Lemma 1 presents another combinatorial property of a matrix containing entries equally colored white and black. In comparison with [16] we present another proof that gives us a better c = • One can choose m rows, and in every of these rows a white and a black entry, such that all these 2m entries are in different columns.…”
Section: Technical Lemmasmentioning
confidence: 99%
See 1 more Smart Citation